Degradation of Erythromycin in Seafood Products by Different Thermal Treatments - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2020)
Prawn (Macrobrachium rosenbergii) and tilapia (Oreochromis niloticus) are two important seafood farming species cultivated in Mekong river delta, Vietnam. Intensive aquaculture of these species has high risk of disease outbreaks caused by virus, bacteria, fungi, and other pathogens. Erythromycin is the most widely used antibiotic in the macrolide. Erythromycin has a low cytotoxicity for aquaculture. Prawn and tilapia intended for export have to meet the antibiotic residue standards of the importing countries. In the present research, different factors affecting erythromycin residue on prawn and tilapia muscles after thermal treatments were carefully investigated. The present results proved that among frozen, cooked, oil-fried and baked methods; the oil-frying treatment strongly degraded erythromycin at 86.88% in prawn and 87.02% in tilapia samples. Thermal processing by oil heating medium at high temperature caused a significant degradation in the concentration of erythromycin residue.Keywords: Prawn, Tilapia, Erythromycin, Thermal, Degradation, Antibiotic residue.